Norwegian Bokmål: Hvite og røde peoner Painting title... - Eugène Delacroix (Wikimedia Commons, 1848)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Norwegian Bokmål: Hvite og røde peoner Painting title....
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures